2021
DOI: 10.1039/d1tc01673c
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced electron transfer in mechanically interlocked suit[3]ane systems

Abstract: Suitanes, a new class of two-component mechanically interlocked systems, have recently been developed. In this work, we report a detailed study of photoinduced electron transfer processes in the suit[3]anes consisting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Typically, excited CT states decay to the ground state by charge recombination. The effect of internal geometry reorganization on ∆G 0 is rather small for large π-conjugated systems, such as the complexes studied, and can be safely ignored [65,78]. The computed charge recombination rates (k CR ) are provided in Table 4.…”
Section: Complexmentioning
confidence: 99%
“…Typically, excited CT states decay to the ground state by charge recombination. The effect of internal geometry reorganization on ∆G 0 is rather small for large π-conjugated systems, such as the complexes studied, and can be safely ignored [65,78]. The computed charge recombination rates (k CR ) are provided in Table 4.…”
Section: Complexmentioning
confidence: 99%
“…Note that the rates of ET and CR processes were computed in the Franck‐Condon region. We have previously shown that the effect of internal geometry reorganization on ΔG 0 is rather small for large conjugated systems such as fullerenes and their inclusion complexes [48,49] . The use of the FCD model, based on the unitary transformation of adiabatic states into diabatic ones, makes it possible to estimate the coupling beyond the crossing point.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the effect of internal geometry reorganization on ΔG 0 is rather small for large conjugated systems such as fullerenes and their inclusion complexes. [48,49] The use of the FCD model, based on the unitary transformation of adiabatic states into diabatic ones, makes it possible to estimate the coupling beyond the crossing point. The FCD method provides good estimates of the coupling and is recommended for extended molecular systems.…”
Section: Electron Transfer Ratesmentioning
confidence: 99%
“…For large conjugated systems, the effect of internal geometry reorganization on DG 0 is rather small and can be safely neglected. 61,62 However, in the studied complexes, the Bowl fragment is relatively small, and the relaxation effect can be signicant. Thus, we studied the effect of geometry relaxation on the rate of charge recombination in DCM for rim-NCorIC 60 , hub-NCorIC 60 , PP-bowlIC 60 , Hyd-bowlIC 60 , Cyc-bowlIC 60 , and SumIC 60 (Table 4).…”
Section: Electron Transfer Rates and The Effect Of Excited State Geom...mentioning
confidence: 94%